1996
DOI: 10.1063/1.871917
|View full text |Cite
|
Sign up to set email alerts
|

Mode coupling effects on resistive wall instabilities

Abstract: It is shown that destabilization of resistive wall magnetohydrodynamic (MHD) modes in the presence of rotation is a mode coupling phenomenon. Based on this observation, certain unanticipated effects are readily explained. These include the fact that resistive wall modes with rotation can be unstable, even for parameters for which the MHD modes are stable with the wall at infinity, and the fact that this destabilization depends critically on the plasma parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 13 publications
8
29
1
Order By: Relevance
“…A similar result has been obtained before. 17 This result has a simple physical explanation. The dispersion relation Eq.…”
Section: ͑90͒mentioning
confidence: 82%
See 1 more Smart Citation
“…A similar result has been obtained before. 17 This result has a simple physical explanation. The dispersion relation Eq.…”
Section: ͑90͒mentioning
confidence: 82%
“…However, some recent studies, 8,17 show that there are parameter regimes where plasma flow and a resistive wall can have a destabilizing effect. In order to isolate this destabilizing effect a very simple configuration was studied in Ref.…”
Section: Discussionmentioning
confidence: 97%
“…This behavior is explained by the mode-coupling picture of Ref. 17 and is even more noticeable for ideal plasma resistive wall modes. 1,17 Larger X is stabilizing for the full MHD model and the expanding stable region develops a tail toward negative G and K. This general behavior of stabilization as X increases is consistent with the observation in Ref.…”
Section: Results With Plasma Rotation and Complex Gain G Imentioning
confidence: 77%
“…1,2,5, 7,8,[11][12][13]17,18,20,23,26,28 Studies have also been performed for reversed field pinches (RFPs). 4, 39,40 Earlier studies in tokamak geometry 3, 6,9,10,14,30,38 investigated sensing either the radial or the poloidal component of the magnetic field, concluding that it is better to sense the poloidal component, and that the latter measurement is of more use if it is inside the wall.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in the parameter range for which the resistive plasma form of the mode ͑''tearing''͒ is wall stabilized, it appears to be possible to stabilize the mode over a large parameter range with slow rotation frequencies, of the order of the nominal tearing growth rate. [31][32][33][34][35] These results suggest that rotational stabilization of the resistive wall mode is too delicate and requires too much rotation above the ideal plasma threshold ͑with wall at infinity͒, but that actual devices might be operated at parameters for which the resistive plasma form of the mode is wall stabilized. Since the external kink is a resonant mode ͑i.e., has mode rational surfaces in the plasma but is not an internal mode͒ more recent studies have found that it can be stabilized by slow ͑tearing rate͒ rotation, above the ideal plasma ␤ limit with the wall at infinity in the range of parameters for which the resistive plasma form of the mode is also wall stabilized.…”
Section: Introductionmentioning
confidence: 91%